Case reportAtypical coronary veins anatomy as an obstacle for cardiac resynchronization therapy – case report - Markuszewski, Leszek; Rosiak, Marcin; Bissinger, Andrzej; Chudzik, Michał (Archives of Medical Science, 2005)
Background: Cardiac resynchronization therapy (CRT) is a standard for end-stage heart failure patients. During CRT procedure, left ventricular lead is positioned through coronary sinus (CS) in a coronary vein. Case report: 51-year-old man with dilated cardiomyopathy and persistently symptomatic heart failure despite medical therapy was referred for implantation of CRT system. During CRT procedure, CS ostium was localized and venography was performed. Anatomical variant of CS with lack of typical wide venous trunks was revealed. Instead narrow coronary veins and large venous sinus appeared. Despite 60- -minutes lasting fluoroscopy it was not possible to guide the lead across venous structures. Conclusion: Atypical CS anatomy presenting as venous sinuses could be a serious obstacle for CRT.